2017
DOI: 10.1002/pros.23435
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of epithelial‐mesenchymal‐transition (EMT) signature and PARP‐1 in prostate cancer radioresistance

Abstract: Our results suggest that EMT programming effectors, integrated with the actin cytoskeleton regulator cofilin and mesenchymal PARP-1 expression profile provide a signature of potential predictive significance of therapeutic response to radiotherapy in a subset of prostate cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
(126 reference statements)
0
26
0
1
Order By: Relevance
“…This specific adjuvant treatment benefits patients with defective DNA-damage repair such as the BRCA1 and BRCA2 mutations that frequently occur in breast and ovarian cancers [20,21]. Studies involving PARPi for the treatment of PCa are already underway [22,23]. In this context, one strategy for the discovery of new cancer biomarkers and/or potential therapeutic targets is to integrate genomic data from genetically engineered mouse models (GEMMs) and human cancer patients [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This specific adjuvant treatment benefits patients with defective DNA-damage repair such as the BRCA1 and BRCA2 mutations that frequently occur in breast and ovarian cancers [20,21]. Studies involving PARPi for the treatment of PCa are already underway [22,23]. In this context, one strategy for the discovery of new cancer biomarkers and/or potential therapeutic targets is to integrate genomic data from genetically engineered mouse models (GEMMs) and human cancer patients [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it is associated with a younger age of occurrence and is diagnosed as diffuse-type at stage III/IV, showed a significantly higher recurrence rate, higher probability of developing peritoneal seeding at the first site of recurrence, and extremely poor survival compared to other subtypes. Furthermore, it has been reported that PARP-1, which is involved in the mechanism of radiation induced DNA damage repair, is increased in the mesenchymal phenotype, and it could reduce the cell killing effects of RT in prostate cancer [7,8]. In addition, hypoxia, which is a hallmark of tumor and the most important cause of radioresistance, was reported to be associated with the loss of E-cadherin [9].…”
Section: Discussionmentioning
confidence: 99%
“…The planned treatment was completed in 75.4% of patients in the XP arm and 81.7% in the XP-RT arm [11]. Other details of the ARTIST trial, including chemotherapy and RT protocols, were described in previous reports [8][9][10]. From the 458 patients enrolled, 106 tissue samples of 359 patients except 99 patients with stage I were available for evaluation in the present study.…”
Section: Patients and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Black men with PCa are also 27% more likely to stain positive for AR and have 81% greater nuclear expression of AR 14 , 47 . The “EMT signature” also appears to correlate with resistance to radiation therapy and anti-androgens in a subset of PCa patients 48 . With this increased androgen responsiveness, one could posit that the tumorigenic epithelial cells within Black men would more likely undergo EMT and, thereby distant disease spread as a direct result of increased concentrations of TILs in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%